2018
DOI: 10.1021/jacs.8b06095
|View full text |Cite
|
Sign up to set email alerts
|

Non-heme High-Spin {FeNO}6–8 Complexes: One Ligand Platform Can Do It All

Abstract: Heme and non-heme iron-nitrosyl complexes are important intermediates in biology. While there are numerous examples of low-spin heme iron-nitrosyl complexes in different oxidation states, much less is known about high-spin (hs) non-heme iron-nitrosyls in oxidation states other than the formally ferrous NO adducts ({FeNO} in the Enemark-Feltham notation). In this study, we present a complete series of hs-{FeNO} complexes using the TMGtren coligand. Redox transformations from the hs-{FeNO} complex [Fe(TMGtren)(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
85
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(96 citation statements)
references
References 122 publications
9
85
1
Order By: Relevance
“…[14] Similar reactivity is observed for our new hs-{FeNO} 7 complex [Fe(BMPA-tBu 2 PhO)(NO)(OTf)] (3), which contains the weak field ligand [N-(3,5-di-tert-butyl-2-hydroxybenzyl)-N,N-di-(2-pyridylmethyl)]amine (BMPA-tBu 2 PhOH). Previous studies have shown fast DNIC formation following reduction of our hs-{FeNO} 8 model complex, [Fe(TMG 2 dien)(NO)] + .…”
supporting
confidence: 79%
See 2 more Smart Citations
“…[14] Similar reactivity is observed for our new hs-{FeNO} 7 complex [Fe(BMPA-tBu 2 PhO)(NO)(OTf)] (3), which contains the weak field ligand [N-(3,5-di-tert-butyl-2-hydroxybenzyl)-N,N-di-(2-pyridylmethyl)]amine (BMPA-tBu 2 PhOH). Previous studies have shown fast DNIC formation following reduction of our hs-{FeNO} 8 model complex, [Fe(TMG 2 dien)(NO)] + .…”
supporting
confidence: 79%
“…Clearly,more work is necessary to elucidate the biologicallyrelevant reactivity of non-heme hs-{FeNO} 8 complexes. [14] Herein, we further investigated the reactivity of hs-{FeNO} 8 complexes with TPA( tris(2-pyridylmethyl)amine) and related coligands.I np articular, we report the serendipitous discovery of aF e 2 (NO) 2 diamond core structure,w hich is unprecedented in non-heme iron-NO chemistry.T his core structure is stabilized by ac hange in spin state of the iron centers to low-spin (ls) Fe II .Incontrast, aTPA derivative with aw eaker ligand field that cannot support the spin-state change to ls proceeds to DNIC formation. [10] In addition, DNICs with histidine ligation have been proposed to form at the non-heme diiron core of the ferric uptake regulation protein (Fur), [11] in serum albumin, [12] and in ferritin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…67, 69-71 We cannot rule out the possibility of X-ray induced reduction of the Fe center to generate an {FeNO} 8 species that would be anticipated to display such an acute Fe-N-O angle. 70,71 Alternatively, it is noteworthy that the NO ligand occupies a rather confined pocket defined by the Tyr70 side chains which may impose steric constraints on the ligand geometry.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27] Lehnert group reported the first series of high-spin {FeNO} [6][7][8] complexes and demonstrated that the redox transformation of high-spin {FeNO} [6][7][8] were all ironbased contrasted to corresponding low-spin complexes where redox transformation was generally NO centered. 28 Most recently, Meyer and coworkers synthesized an complete series of five {FeNO} [6][7][8][9][10] complexes with one ligand scaffold. 29 While significant progress has been made in the chemistry of nonheme iron and NO reaction, the transformation from {FeNO} 7 to {Fe(NO) 2 } 9 has been rarely reported.…”
Section: Introductionmentioning
confidence: 99%